University and Research Libraries in Europe Working towards Open Access - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
This paper presents an overview of ways in which LIBER (Association of European Research Libraries) and its members are working towards embedding Open Access approaches to the dissemination of research outputs. It does this in three ways — by looking at current debates in which LIBER has become interested, on the economics of Open Access; by highlighting new projects in which LIBER is engaged, to develop new models and services via Open Access; and by looking at a model of best practice amongst LIBER members for developing an institutional Open Access mandate. The paper ends by drawing conclusions about the vitality of the work of LIBER member libraries in the Open Access landscape.